Modeling methods for medical systems biology : regulatory dynamics underlying the emergence of disease processes /: regulatory dynamics underlying the emergence of disease processes. ([2018]) - Alvarez-Buylla, Elena; Martínez-García, Juan Carlos; Dávila-Velderrain, José; Domínguez-Hüttinger, Elisa; Martínez-Sánchez, Mariana Esther
No abstract available